2017
DOI: 10.15537/smj.2017.8.18456
|View full text |Cite
|
Sign up to set email alerts
|

Level of evidence of abdominal surgery clinical research in Saudi Arabia

Abstract: Objectives:To quantify and evaluate the level of evidence (LOE) of Saudi publications in abdominal surgery and correlate the obtained results with that of other similar national and international studies.Methods:Study design was a systemic review. Literature search strategy was developed to retrieve available articles between January 2000 and December 2016 that are related to abdominal surgery utilizing PubMed and Google Scholar. Retrieved articles were analyzed in depth with several parameters, then evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…These findings are closely related to the current study, where the source of information is textbooks. Makhdom et al reported that engagement in clinical orthopedic research was also low in Saudi Arabia [ 19 ]. A review involving 91 orthopedic surgeons and 251 articles showed that the evidence collected within 20 years was low compared to the studies conducted in North America [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are closely related to the current study, where the source of information is textbooks. Makhdom et al reported that engagement in clinical orthopedic research was also low in Saudi Arabia [ 19 ]. A review involving 91 orthopedic surgeons and 251 articles showed that the evidence collected within 20 years was low compared to the studies conducted in North America [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Makhdom et al reported that engagement in clinical orthopedic research was also low in Saudi Arabia [ 19 ]. A review involving 91 orthopedic surgeons and 251 articles showed that the evidence collected within 20 years was low compared to the studies conducted in North America [ 19 ]. A leading factor for the sparse evidence in orthopedic research conducted in Saudi Arabia was inadequate funding to support research assistants.…”
Section: Discussionmentioning
confidence: 99%
“…Other multiple studies examined the publications by Saudi surgeons and physicians on plastic, orthopedic, epilepsy, gastroenterology, spine, and abdominal surgery [ 14 - 19 ]. Their findings were mostly consistent with our findings in this study in regard to LOE and lack of clinical randomized trials.…”
Section: Discussionmentioning
confidence: 99%
“…5 The choice of using it was based on similar previously reported studies. [6][7][8][9][10][11] Similarly, the impact factor should not be considered an absolute measure of research impact. There are other more sophisticated measures of quality and impact of healthcare research.…”
Section: Muneera Al Hussain Department Of Internal Medicine Price Sulmentioning
confidence: 99%